Perspectives of the Swiss policy towards the European Union - Tomczyk, Michał (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
Relations between Switzerland and the European Union might be perceived as interesting, and at the same time an unprecedented example of the new, flexible integration. Despite more than a decade of fruitful cooperation, many of its aspects remains controversial. The problem of autonomous adaptation, lack of ability to influence decision-making processes within the Community, the opening of the labor market for new EU member states or other institutional aspects of the implementation of the agreements. These are just a part of the problems, which could be mentioned here. So the basic question remains – what will happen next? Has this an unprecedented example of a new form of integration reached its limits? What could be the prospects for the future cooperation? This article attempts to find answers to these questions. Several scenarios are taking under consideration, based on an analysis of current conditions and experiences, as well as on evaluation of the current political strategy of the government. That is: continuation of the bilateral relations, the accession to the European Union or the conclusion of a framework or association agreement. Those scenarios are being analysed in order to find the most probably solution for the future relations between European Union and Switzerland.

Stosunki między Szwajcarią a Unią Europejską mogą być postrzegane jako interesujące, a jednocześnie jako bezprecedensowy przykład nowej, elastycznej integracji. Mimo ponad dekady owocnej współpracy, wiele jej aspektów pozostaje kontrowersyjnymi. Problem autonomicznej adaptacji, braku możliwości wpływania na procesy decyzyjne na terytorium Wspólnot, otwarcia rynku pracy dla obywateli nowych państw członkowskich UE lub inne problemy związane z instytucjonalnym wymiarem realizacji umów. To tylko część problemów, które mogą być wymienione w tym kontekście. Można więc postawić zasadnicze pytanie: co będzie dalej? Czy ten bezprecedensowy przykład nowej formy integracji osiągnął już swoje granice? Jakie mogą być perspektywy przyszłej współpracy? Celem niniejszego artykułu jest próba znalezienia odpowiedzi na powyższe pytania. W rozważaniach uwzględniono kilka scenariuszy, będących wynikiem analizy aktualnych warunków i doświadczeń, jak również na oceny bieżącej strategii politycznej szwajcarskiego rządu. Mowa o: kontynuacji stosunków dwustronnych, przystąpieniu do Unii Europejskiej lub zawarciu umowy ramowej czy też stowarzyszenia. Scenariusze te są analizowane w celu znalezienia odpowiedzi na pytanie o najbardziej prawdopodobny przebieg przyszłych stosunków między Unią Europejską a Szwajcarią.
Perspektywy szwajcarskiej polityki wobec Unii Europejskiej
Keywords: European Integration; European Union; Swiss policy; bilateral agreements; integracja europejska; Unia Europejska; polityka szwajcarska; umowy bilateralne